"I'm doing really well in this sport, but I'm still pretty doing it": Gender performance among adolescent female athletes - Golbe, Susan H. (Tufts Archival Research Center, 2005)
Research on the gender performance of female athletes stemming from a sex role socialization theory perspective finds a conflict between being a girl or woman and being an athlete, which is not supported by most recent empirical research on female athletes, and fails to consider the ways in which female athletes construct their own gender performances. Drawing on West and Zimmerman's pivotal work on doing gender (1987), this research seeks to fill this gap. Drawing on fieldwork and qualitative interviews with members of a regional U-18 softball team and a high school varsity basketball team over the course of their season, I show that there are a variety of ways in which adolescent female athletes manage being a girl and being an athlete. Through their actions, the athletes I observed were redefining what it meant to be a girl by being an athlete at the same time. Sometimes, they separated their gendered performances into different contexts. Other times, gender was just not a salient performance. Most importantly, some of the athletes blended aspects of a normatively feminine gender performance with aspects of being an athlete to create a new gendered category of female athlete.